Sistem Informasi Teknologi Inovasi untuk Mendukung Pengembangan Agroindustri di Kawasan Lahan Pantai - Lilik Sutiarso; Sigit Supadmo Arif; P. Tamtomo; Riki Andika (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2010)
Recently, the main challenge in the development of agricultural industry sector is the limited presence of the natural resources of agriculture, both in quantity and quality aspects. One of the natural resources that significantly degrade is an agricultural land area. The research was conducted for identifying the capacity of coastal area as one of the natural resources to support development of an agro-industry through introducing agricultural innovation technology. In this stage, outputs of the research were an information system for managing those innovation technologies and profile of the farming system in coastal area.Research mechanisms include: (i) identification of system parameters through field observations, (ii) preparation of model development system, (iii) development of software-based GIS, (iv) validation and verification of systems with field data acquisition, and (v) standardization system. The developed model was tested in three districts in Province Yogyakarta, namely (i) Bantul, (ii) Kulon Progo and (iii) Gunungkidul.ABSTRAKTantangan utama dalam pembangunan industri pertanian adalah semakin terbatasnya keberadaan sumberdaya alam pertanian, baik dalam aspek kualitas maupun kuantitasnya. Salah satu sumberdaya alam yang secara signifikan men- galami degradasi eksistensinya yaitu lahan pertanian. Penelitian ini dilakukan untuk mengidentifikasi kemampuan sumberdaya lahan pantai dalam mendukung pengembangan agroindustri melalui introduksi berbagai teknologi ino- vasi bidang pertanian. Dalam tahapan ini, keluaran dari hasil penelitian merupakan sistem informasi yang bertujuan untuk mengelola teknologi inovasi tersebut yang disertai dengan profil usaha tani di wilayah lahan pantai.Mekanisme penelitian yang dilakukan meliputi; (i) identifikasi parameter sistem melalui observasi lapangan, (ii) pe- nyusunan model pengembangan sistem, (iii) pengembangan perangkat lunak sistem informasi yang berbasis GIS, (iv) validasi dan verifikasi sistem dengan pengambilan data lapangan, dan (v) pembakuan sistem. Uji coba sistem diaplikasikan di tiga kabupaten yang ada di Prop. DIY, yaitu (i) Kab. Bantul, (ii) Kab, Kulon Progo dan (iii) Kab. Gunungkidul.